2003
DOI: 10.1159/000073024
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Uraemic Toxins with Activated Carbon Restores the Functional Properties of Albumin

Abstract: Background: Previous work has demonstrated that a partial normalization of the conformation of albumin from uraemic plasma and a substantial restoration of its binding abilities can be achieved by extraction with activated charcoal. This is best achieved at pH 3, but exposure of whole plasma to this low pH leads to the loss of some essential components. Methods: The melting curves and ligand-binding abilities of uraemic albumin have been investigated after extraction with a new generation of activated carbon a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…hippuric acid (HA), indoxyl sulfate (IS), 3carboxy-4-methyl-5-propyl-2-furanpropionic acid (CMPF), indole-3 acetic acid (IAA), etc. 17 However, from the available literature, it is found that FUR binds to site I of HSA 11,16,18 whereas all predominant uremic toxins except CMPF bind mainly to site II of HSA. 19−21 So, only CMPF is the uremic toxin that directly inhibits the binding of FUR to albumin as they share the same binding site.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…hippuric acid (HA), indoxyl sulfate (IS), 3carboxy-4-methyl-5-propyl-2-furanpropionic acid (CMPF), indole-3 acetic acid (IAA), etc. 17 However, from the available literature, it is found that FUR binds to site I of HSA 11,16,18 whereas all predominant uremic toxins except CMPF bind mainly to site II of HSA. 19−21 So, only CMPF is the uremic toxin that directly inhibits the binding of FUR to albumin as they share the same binding site.…”
Section: Introductionmentioning
confidence: 99%
“…First, it may be due to some conformational changes in albumin under chronic renal disease but putative structural modifications of pathological HSA have been disputed for decades. Second, according to the most accepted hypothesis, HSA binding sites might be occupied by uremic toxins, viz. hippuric acid (HA), indoxyl sulfate (IS), 3-carboxy-4-methyl-5-propyl-2-furanpropionic acid (CMPF), indole-3 acetic acid (IAA), etc . However, from the available literature, it is found that FUR binds to site I of HSA ,, whereas all predominant uremic toxins except CMPF bind mainly to site II of HSA. So, only CMPF is the uremic toxin that directly inhibits the binding of FUR to albumin as they share the same binding site.…”
Section: Introductionmentioning
confidence: 99%
“…The combination of unspecific adsorptive properties of activated carbonic matrix with the specific adsorption of DNA-coupling substances demonstrates a number of positive clinical effects of the usage of such hemoimmunoadsorbents in the treatment of exacerbations of severe psoriasis and, especially, psoriatic arthropathy, bronchial asthma, lupus nephritis, etc. These adsorptive materials were successfully used for extraction of the most typical protein-bound toxins from blood plasma of patients with hepatic and renal insufficiency Sarnatskaya et al, 2002Sarnatskaya et al, , 2003. Recently, the new type of high-porous carbonic adsorbents having specific internal surface up to 5000 m 2 per 1 g was synthesized in the form of light beads of the regular spherical shape with pronounced mass-fractal organization of its internal dimension.…”
Section: Introductionmentioning
confidence: 99%